A juventude fora da CASA: os jovens egressos do Centro de Atendimento Socioeducativo ao Adolescente - Fundação CASA - Gonçalves, Rosângela Teixeira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Brazilian childcare system has experienced significant growth in the number of young people fulfilling educational measures commital. As even before the regulations of the Statute of Children and Adolescents and the National Socio-Educational Services System, which point to the commital only in the latter case, the socio-educational institutions of deprivation of liberty were consolidated in the country and in greater numbers in the state of São Paulo. They can, this research aimed to bring the profile, the trajectory and the representations of young egression of social and educational units of the CASA Foundation, over the period of performance of the detention procedure and socio-educational measures in freedom of probation. As conclusions, the research shows that the practices of the former FEBEM, still remain in force in the daily lives of male and female units of the CASA Foundation and representations of young people on the institution. When released, the socio-educational measure of commital increases the positive status of young people against the crime and the negative status front of the school and the world of work. And the measure of probation that it could enable the experience of other paths for young people entered the educational measures, is becoming as an extension of the sentence, which increases the chance of recurrence and institutionalization.

O sistema socioeducativo brasileiro tem experimentado um crescimento significativo no número de jovens cumprindo medidas socioeducativas de internação. Pois, mesmo diante das normativas do Estatuto da Criança e do Adolescente e do Sistema Nacional de Atendimento Socioeducativo, que apontam para a internação somente em último caso, as instituições socioeducativas de privação de liberdade se consolidaram no país e em maior número no estado de São Paulo. Desse modo, a presente pesquisa teve como objetivo trazer o perfil, a trajetória e as representações dos jovens egressos das unidades socioeducativas da Fundação CASA, sobre o período de cumprimento da medida de internação e da medida socioeducativa em meio aberto de Liberdade Assistida. Como conclusões, a pesquisa aponta que as práticas da antiga FEBEM, ainda permanecem vigentes no cotidiano das unidades masculinas e femininas da Fundação CASA e nas representações dos jovens sobre a instituição. Quando em liberdade, a medida socioeducativa de internação amplia o status positivo dos jovens frente ao crime e o status negativo frente à instituição escolar e ao mundo do trabalho. E, a medida de LA que poderia vir a possibilitar a vivência de outras trajetórias para os jovens inseridos nas medidas socioeducativas, vem se constituindo como uma ampliação da pena, que aumenta a possibilidade de reincidência e de institucionalização.
Keywords: Fundação Centro de Atendimento Socioeducativo ao Adolescente; Delinquentes juvenis; Juventude; Assistência a menores; Jovens - Conduta; Juvenile delinquents